Fat-Water Separation with High Temporal and Spatial Resolution for Abdominal MRI during Free Breathing - Ababneh, Riad; Benkert, Thomas; Breuer, Felix (Jordan Medical Journal, 2017)
Objective: To separate the fat and water contents in the abdomen during free breathing at high temporal and high spatial resolution by employing radial sampling with a golden angle increment. Materials and Methods: A radial fast imaging with steady-state free precession (TrueFISP) sequence was used and modified to allow for different echo times (TEs) for subsequent radial projections for fat-water separation. The k-space-weighted image contrast (KWIC) radial filtering technique was applied to enable high temporal as well as high spatial resolution. Finally, principal component analysis (PCA) was performed along the dynamic image series in order to reduce image streaking and enhance the signal-to-noise ratio (SNR). Results: The approach was combined with the KWIC filter and provided good fat-water separation with a robust high temporal ( 100 ms) and high spatial resolution. Results for the abdomen with free breathing are presented. Conclusion: Good separation of fat and water signals was achieved using the radial TrueFISP sequence during free breathing